2021
DOI: 10.24193/adn.14.1.7
|View full text |Cite
|
Sign up to set email alerts
|

What are the Purposes of Teachers for Using the eTwinning Platform and the Effects of the Platform on Teachers?

Abstract: This study is a qualitative case study research, determining the purposes of teachers to use the eTwinning platform and to examine the effects of the platform on teachers. The study group consisted of 15 volunteer teachers who carried out eTwinning projects rewarded with quality labels. In the study, the data were obtained through a semi-structured interview form, and the content analysis method was used in the data analysis. According to the results obtained, it was concluded that teachers used the eTwinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 11 publications
2
7
0
6
Order By: Relevance
“…In turn, the best way to learn science is to practice the different ways of doing, talking and thinking about science in the classroom and consistently the students interviewed valued the opportunity to participate in the research project. Moreover, the results of this study, which deals with the improvement of the pre-service teachers' knowledge of the pedagogical affordances of the platform, are in line with the conclusions of the study by Acar and Peker (2021), in which in-service teachers from different subject areas report on the contribution of eTwinning to their professional development and collaboration as well as to their personal development.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In turn, the best way to learn science is to practice the different ways of doing, talking and thinking about science in the classroom and consistently the students interviewed valued the opportunity to participate in the research project. Moreover, the results of this study, which deals with the improvement of the pre-service teachers' knowledge of the pedagogical affordances of the platform, are in line with the conclusions of the study by Acar and Peker (2021), in which in-service teachers from different subject areas report on the contribution of eTwinning to their professional development and collaboration as well as to their personal development.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, the study by Huertas-Abril and Palacios-Hidalgo (2023) reports on the improvement of language teachers' digital skills through eTwinning activities. Acar and Peker (2021), based on interviews with in-service teachers from different subject areas, found that eTwinning activities contribute to their professional development and collaboration. Moreover, the platform makes a great contribution to the teachers, both personally and professionally.…”
Section: Digital Competencementioning
confidence: 99%
“…Alanyazında eTwinning'in öğretmenlerin dijital becerilerini geliştirdiği yönünde çeşitli çalışmalar mevcuttur. Crişan (2013), eTwinning projelerini aktif olarak yürüten öğretmenlerin profesyonel gelişimleri için BİT'i daha iyi kullandıkları sonucuna varmıştır. Kampylis vd.…”
Section: Gerekçe Ve öNemunclassified
“…Yapılan araştırmalarda eTwinning projelerinin; teknoloji entegrasyonunu desteklediği, Web.2.0 araçlarının kullanımına önem verdiği öğrenci ve öğretmenlerin dijital becerilerini geliştirdiği vurgulanmaktadır (Crişan, 2013;Scoda, 2013;Velea, 2011;Vourikari vd., 2011). Ancak bu durumu dijital yeterliklere ilişkin geliştirilen çerçeve ve modeller kapsamında açıklayan çalışma sayısı oldukça azdır.…”
Section: Gerekçe Ve öNemunclassified
“…eTwinning contributes to the development of participants' ICT skills and language skills (Demir, 2019), the development of high-level skills such as creativity, teamwork, decision making and problem-solving (Avcı, 2021), and the increase in interest in technology (Çetin Cengiz and İzci, 2021). Teachers and ITE trainers increase their pedagogical and technological knowledge and competencies and develop innovative perspectives (Acar & Peker, 2021;La Marca & Gulbay, 2021). Collaborative tasks in projects not only encourage student teachers to develop the professional skills they need to set precise goals, be extremely specific in planning, programming and documenting their work, but also in with teamwork, more specifically listening to the perspectives, perspectives and suggestions of international partners (Tonner-Saunders & Shimi, 2021).…”
Section: Literaturementioning
confidence: 99%